Synthesis and photophysical properties of bis-tetraphenylene-diones. Issue 27 (2nd July 2020) - Shi, Yaxin; Li, Zhi
Graphical abstract: Highlights: Bis-TPE-diones have been synthesized by F-C acylation in one step for the first time. Our method is more concise than the reported methods. The AIE, solavatochromism and mechanochromism have been studied for the first time. The Bis-TPE-diones could be further applied in optoelectronic devices. Abstract: Bis-tetraphenylethene-diones (Bis-TPE-diones) can serve as key precursors for the synthesis of blue light-emitting OLED materials. In this paper, four Bis-TPE-diones with different dicarbonyl chains as linkers were elaborately designed for photophysical properties investigation. These Bis-TPE-diones have been facilely synthesized by F-C acylation in one step for the first time. Expensive and harmful reagents as well as harsh reaction conditions were excluded, which make our new method more economical and convenient. The AIE properties, solavatochromism and mechanochromism of the Bis-TPE-diones have also been carefully studied. The Bis-TPE-diones exhibited notable AIE properties and their maximum fluorescence in THF can be turned on by low water fractions ( f w, 10%–40%). The f w to turn on the maximum fluorescence are closely associated with the dicarbonyl chain linkers in the Bis-TPE-diones as the following sequence: conjugate chain (fumaryl, f w  = 10%) < flexible long chain (succinyl, f w  = 20% < glutaryl, f w  = 30%) < short chain (1, 2-dicarbonyl, f w  = 40%). This result could be ascribed to different polarities and conformations of the Bis-TPE-diones. Therefrom, a new strategy to turn on the maximum fluorescence of AIE-gens was proposed: The f w to turn on the maximum fluorescence of AIE-gens could be tuned by adjusting the length and the conjugation of the linker. This strategy could be instructive for design of other AIE molecules. The Bis-TPE-diones also exhibited notable solvatochromism, observable mechanochromism as well as good thermal stability. With these outstanding properties, the Bis-TPE-diones could be further applied in optoelectronic devices and other functional materials.